On agency and empowerment in a #MeToo world. Issue 8 (5th November 2018) - Ozkazanc‐Pan, Banu
Abstract : In the midst of the #MeToo movement sweeping across different societies, what opportunities and challenges exist for changing extant gender structures and systems that have allowed for sexual harassment and assault to take shape? Such a discussion provokes questions around what kinds of feminisms, both as philosophical traditions and as a set of praxis/practices, enable societal and organizational change. This article focuses explicitly on different notions of agency deriving from various feminist traditions to underscore possibilities for engaging in such change. Borrowing from intersectional, decolonial, postcolonial and transnational feminist perspectives, I suggest that a collectivist approach to agency is necessary for gender system change. I coin collective feminism as a way to conceptualize agency that only becomes possible through the work of many and then discuss this mode of feminism in relation to empowerment and social change toward gender equality.